2020
DOI: 10.14730/aaps.2019.01928
|View full text |Cite
|
Sign up to set email alerts
|

Short-term safety of facial rejuvenation using an absorbable polydioxanone monofilament thread in patients with mild-to-moderate facial skin sagging

Abstract: Background Facial rejuvenation techniques using thread lifts are performed by passing sutures under the facial skin to treat sagging and facial flaccidity, and their advantages include a relatively short recovery time and relatively small incisions. In this study, we describe the short-term safety of a facial rejuvenation technique involving an absorbable polydioxanone monofilament thread (Mint Lift) in patients with mild-to-moderate facial skin sagging. Methods The current multicenter, retrospective, case-ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 23 publications
0
15
0
2
Order By: Relevance
“…For facial rejuvenation procedures using the Mint Lift ® , the entry and exit points are determined to prepare holes for insertion of a threadlift considering anatomic characteristics of the face, as previously described 38,39 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For facial rejuvenation procedures using the Mint Lift ® , the entry and exit points are determined to prepare holes for insertion of a threadlift considering anatomic characteristics of the face, as previously described 38,39 …”
Section: Resultsmentioning
confidence: 99%
“…47 findings, they concluded that facial rejuvenation using the Mint Lift ® 43 and 17 might be a safe modality. 38 Finally, Moon et al recently reported that there were a total of 4 cases (19.0%) of postoperative complications, all of which were spontaneously resolved within a maximum period of 4 months. 39 The effects of threadlifting have been explored; Kim et al showed that a threadlift reacted with the adjacent soft tissue and thereby produced additional lifting effects after it directly pulled the skin, followed by the increased synthesis of type I collagen and transforming growth factor-β1 (TGF-β1).…”
Section: Anatomic Considerations In Determining the Entry And Exit Pointsmentioning
confidence: 97%
See 2 more Smart Citations
“…Of various types of PDO thread-lifts, the Mint Lift ® (HansBiomed Co., Ltd., Seoul, Korea) deserves special attention because it was approved by the U.S. Food and Drug Administration (US FDA) [11]. Moreover, its clinical efficacy and safety have been well described in the literature [4,[12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%